2017
DOI: 10.1371/journal.pone.0181836
|View full text |Cite|
|
Sign up to set email alerts
|

HBV infection in untreated HIV-infected adults in Maputo, Mozambique

Abstract: BackgroundHIV/ HBV coinfected patients are at high risk of developing chronic HBV infection, liver cirrhosis and hepatocellular carcinoma. In Mozambique, where HIV prevalence is one of the highest in the world, HIV-infected patients are scarcely characterized in terms of HBV coinfection and 3TC-resistance mutations profile.MethodsTo characterize ART-naïve HIV-infected adults, with and without HBV coinfection, a cross-sectional study was conducted between May and November 2012 in two health centers from Maputo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
6
23
0
Order By: Relevance
“…prevalence in other cohorts of co-infected treated patients [10] [14] [24] [44] but similar to that between 50% and 71% in patients infected with HBV alone [31] [45] [46]. Also, these prevalences data are higher than those reported from Maputo, where less than 1% of co-infected subjects carried the marker for HBV immunization [23]. This loss of immunity against hepatitis B was explained by the fact that HIV infection leads to immunosuppression which would reduce the reaction.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…prevalence in other cohorts of co-infected treated patients [10] [14] [24] [44] but similar to that between 50% and 71% in patients infected with HBV alone [31] [45] [46]. Also, these prevalences data are higher than those reported from Maputo, where less than 1% of co-infected subjects carried the marker for HBV immunization [23]. This loss of immunity against hepatitis B was explained by the fact that HIV infection leads to immunosuppression which would reduce the reaction.…”
Section: Discussionsupporting
confidence: 73%
“…Male sex was associated to co-infection significantly with co-infection as has been reported in Benin [28], Nigeria [31], South Africa [27], Rwanda [29] and Cameroon [19]. Other authors have reported a female predominance in Mozambique and Zambia [16] [23], Uganda [17], and in South Kivu [12]. In observing our study population, there were a large number of female than male patients.…”
Section: Discussionsupporting
confidence: 72%
“…Clinically relevant HBV variants include the presence of nucleot(s)ide analogue (NA) resistance mutations (or drug-resistance mutations [DRM]), vaccine escape mutants (VEM), diagnostic escape mutants (DEM), and pre-core (PC)/basal core promoter (BCP) variants that are often reported in association with HCC and risk of cirrhosis (21,22). Moreover, as a result of the HIV epidemic in Sub-Saharan Africa and shared routes of transmission, HBV and HIV co-infection is common (5,(23)(24)(25). Although some HIV antiretroviral medications also have activity against HBV, patients on first-generation anti-HBV therapy with a lower genetic barrier to resistance (ie, lamivudine) may drive selection of HBV-resistant variants (5,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In Mozambique, which has the eighth highest HIV prevalence in the world [ 15 ], the most recent HIV survey showed that the epidemics is getting even worse [ 16 ]. Few studies have been conducted to determine the prevalence of HBV in Mozambique, and they have been conducted in specific groups such as refugees [ 17 ], blood donors [ 18 20 ], HIV infected individuals [ 21 , 22 ] or high risk groups [ 23 ] and showed that the rate varied between 7% and 13%. OBI has received new attention as a serious public health problem.…”
Section: Introductionmentioning
confidence: 99%